1980
DOI: 10.1098/rspb.1980.0058
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and morphogenesis of mammary cellsin vitro

Abstract: Cells of a mammary cell line isolated from a DMBA-induced rat mammary carcinoma undergo differentiation in vitro . A reversible differentiation leads to the formation of two types of microstructure (domes and ridges); this paper is concerned with the mechanism of dome formation. This differentiation is initiated by inducers, some of which are generated in the cultures and act locally; their effect is strongly dependent on cell concentration and requires hydrocortisone. There are, in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…To study the differentiation of the mammary gland, we developed an in vitro model based on two cellular clones, LA7 and 106 (8)(9)(10)(11). We previously showed that dome formation in LA7 cells recapitulates differentiation steps occurring in vivo, when tubules and alveoli develop in the mammary gland at pregnancy and lactation (14,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the differentiation of the mammary gland, we developed an in vitro model based on two cellular clones, LA7 and 106 (8)(9)(10)(11). We previously showed that dome formation in LA7 cells recapitulates differentiation steps occurring in vivo, when tubules and alveoli develop in the mammary gland at pregnancy and lactation (14,18).…”
Section: Discussionmentioning
confidence: 99%
“…This model system is based on two cellular clones, LA7 and 106, both obtained from the parental clone Rama-25, considered to contain stem cells of the rat mammary gland (9)(10)(11)(12)(13). Exposure to lactogenic hormones, lipids, or differentiating agents such as cAMP or DMSO results in the formation of hemispherical polarized structures called ''domes'' in LA7, but not in 106, cells (14,15).…”
mentioning
confidence: 99%
“…For proteomic analysis, cells were cultured in triplicate, each of them derived from a different frozen culture. The LA7 cells, after having grown to confluence, were exposed to 1.5% DMSO as inducer of cell differentiation (13). Cells were harvested by scraping to avoid using trypsin to prevent extracellular protein digestion.…”
Section: Methodsmentioning
confidence: 99%
“…The derived LA7 cell line spontaneously undergoes differentiation in vitro by forming domes, and this differentiation can be strongly promoted by differentiation inducers, such as DMSO. In contrast, the 106 cell line does not undergo this differentiation either spontaneously or under the action of inducers (14)(15)(16). The two cell lines also differ in their ability to produce tumors in nude mice, which is reduced for the LA7 cells (I.Z.…”
mentioning
confidence: 99%
“…WDMN1, originally identified as a gene whose expression is diminished in metastatic rat mammary adenocarcinomas, is a member of a family of protease inhibitors and encodes a secreted protein that may inhibit metastases by inhibiting proteases (19)(20)(21). WDNM1 and ␤-casein genes appear to be specific markers of mammary gland functional differentiation because in vivo the expression of these two genes occurs earlier in pregnancy (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), suggesting that their expression in LA7 cells may be indicative of a possible relationship between the biological processes resulting in dome formation in vitro and the processes resulting in the alveoli differentiation of the mammary gland at pregnancy.…”
mentioning
confidence: 99%